Law’s Symbolic Power: Beyond the Marxist Conception of Ideology - Dębska, Hanna (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
The aim of this paper is to show the symbolic dimension of power developed by Pierre Bourdieu which is simultaneously an insightful break with the well-known Marxist conception of ideology. Bourdieu’s theory is concerned with a profound reflection on relations of power, and particularly the unmasking of those relations that might be deemed as “misrecognised” (ergo, hidden and socially accepted). This is a concept of symbolic power that can be understood as misrecognised and perceived as legitimate authority, or paradoxically denied power. It is a capacity to construct the social reality on the terms of dominant social groups and powerful social institutions, including the institution of law and lawyers. The distinction between “sociodicy” (justification of the social word) and “ideology” is a key element for Bourdieu. Agents of the legal field cannot be simply perceived as a cynical. It is not a “false consciousness” that brings them to impose their symbolic power upon society. The operation of symbolic power is not an instrumental power whereby lawyers intentionally try to impose some propaganda. This power is inscribed both in their dispositions (habitus) and social structure (legal field).
Keywords: symboliczny wymiar władzy; Bourdieu, Pierre